St. Lucia : Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility; Staff Report; Staff Supplement; Press Release; and Statement by the Executive Director for St. Lucia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Sixth Review under the Poverty Reduction and Growth Facility for Benin. Benin's macroeconomic outlook is weaker for 2009-10, reflecting the impact of the crisis. The implementation of structural reforms needs to be accelerated to enhance the competitiveness of Benin's economy and increase its resilience to exogenous shocks. The adoption of a comprehensive strategy for the cotton sector and the implementation of the public finance management action plan are welcome steps.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet